1982
DOI: 10.2307/1938877
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Invertebrate Responses to Size and Density Manipulations of the Common Mummichog, Fundulus Heteroclitus, in an Intertidal Salt Marsh

Abstract: Most studies of the effects of predation on the organization and structure of prey communities have ignored predator population size structure and density. In the present investigation, we designed a series of field experiments to test the effects of these predator population properties on the intertidal benthic invertebrates of a salt marsh. The common mummichog, Fudulus heteroclitus, was the primary predator in our experiments. Three size—classes of mummichogs (small, 40—50) mm Total Length [TL]: medium, 50—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 44 publications
(92 reference statements)
1
39
0
Order By: Relevance
“…Despite very short submersion periods, mullets filter and ingest large quantities of sediment, and concentrate and assimilate organic matter produced by these coastal wetlands, which therefore act as important feeding areas for these species and other exploiting fish species (Laffaille et al, 2001). Although organic matter exportation from salt marshes to sea water by physical vectors such as tidal currents can be significant (Teal, 1962;Nixon, 1980;Gordon & Cranford, 1994), export of organic matter from salt marshes is facilitated by trophic migration of aquatic fauna (Kneib & Stiven, 1982;Kneib, 1987;Lefeuvre et al, 1999) Only a few fish species are able to assimilate salt marsh primary production directly; which is the case for the clupeid Brevoortia patronus in the United States (Deegan et al, 1990) and Liza spp. in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Despite very short submersion periods, mullets filter and ingest large quantities of sediment, and concentrate and assimilate organic matter produced by these coastal wetlands, which therefore act as important feeding areas for these species and other exploiting fish species (Laffaille et al, 2001). Although organic matter exportation from salt marshes to sea water by physical vectors such as tidal currents can be significant (Teal, 1962;Nixon, 1980;Gordon & Cranford, 1994), export of organic matter from salt marshes is facilitated by trophic migration of aquatic fauna (Kneib & Stiven, 1982;Kneib, 1987;Lefeuvre et al, 1999) Only a few fish species are able to assimilate salt marsh primary production directly; which is the case for the clupeid Brevoortia patronus in the United States (Deegan et al, 1990) and Liza spp. in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…In soft-bottom ecosystems like the Rhode River subestuary, predator-prey interactions are particularly complex (sensu Carpenter & Kitchell 1988) because these communities are dominated by guilds of rather generalized predators capable of switching among diverse prey, and because they usually lack a single competitively dominant prey species capable of monopolizing resources (Reise 1978, Virnstein 1980, Kneib & Stiven 1982, Ambrose 1984, Commito & Ambrose 1985 . That is, while predation is often the prevailing control of community structure, a single keystone-like species occurs rarely if at all (Peterson 1979, Levinton 1982.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming apparent that complex trophic interactions occur in infaunal communities (e.g. Commito 1982, Kneib & Stiven 1982, Ambrose 1984b, Commito & Shrader 1985. However, untd it is demonstrated that epibenthic predators take infaunal predators preferentially and that infaunal predators significantly affect nonpredatory infauna, a 2-level model of epibenthic predators and infauna should have primacy as the best general description of marine soft-sediment communities.…”
Section: Discussionmentioning
confidence: 99%